PENGARUH KEPEMILIKAN INTITUSIONAL DAN KUALITAS AUDIT TERHADAP EARNINGS MANAGEMENT DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI - Sri Ayem; Yuliana Adelheit Knoba (SIMAK, 2021)
This research aims to determine the effect of institutional ownership and audit quality on earnings management with financial distress as a moderating variable. The research sample was selected using a purposive technique and taken were the annual financial reports of manufacturing companies that were registered consistently during the last four years, namely 2016-2019 with a sample size of 14. The results of this study indicate that institutional ownership has a negative and significant effect on earning management, audit quality has a negative effect on earnings management, financial distress can moderate the relationship between institutional ownership and earnings management, financial distress can moderate the relationship between audit quality and earnings management